Deployment of Critical Incident Reporting System (CIRS) in public Styrian hospitals: a five year perspective - Gerald Sendlhofer; Peter Schweppe; Ursula Sprincnik; Veronika Gombotz; Karina Leitgeb; Peter Tiefenbacher; Lars-Peter Kamolz; Gernot Brunner (BMC, 2019)
Abstract Background To increase patient safety, so-called Critical Incident Reporting Systems (CIRS) were implemented. For Austria, no data are available on how CIRS is used within a healthcare facility. Therefore, the aim of this study was to present the development of CIRS within one of the biggest hospital providers in Austria. Methods In the province of Styria, CIRS was introduced in 2012 within KAGes (holder of public hospitals) in 22 regional hospitals and one tertiary university hospital. CIRS is available in all of these hospitals using the same software solution. For reporting a CIRS case an overall guideline exists. Results As of 2013, 2.504 CIRS cases were reported. Predominantly, CIRS-cases derived from surgical and associated disciplines (ranging from 35 to 45%). According to the list of hazards (also called "risk atlas"), errors in patient identification (ranging from 7 to 12%), errors in management of medicinal products (ranging from < 5 to 9%), errors in management of medical devices (ranging from < 5 to 10%) and errors in communication (ranging from < 5 to 6%) occurred most frequently. Most often, a CIRS case was reported due to individual error-related reasons (48%), followed by errors caused by organization, team factors, communication or documentation failures (34%). Conclusions In summary, CIRS has been used for 5 years and 2.504 CIRS-cases were reported. There is a steady increase of reported CIRS cases per year. It became also obvious that disregarding guidelines or standards are a very common reason for reporting a CIRS case. CIRS can be regarded as a helpful supportive tool in clinical risk management and supports organizational learning and thereby collective knowledge management.